Copy number variations and founder effect underlying complete IL-10Rβ deficiency in Portuguese kindreds. - Fabienne Charbit-Henrion; Bernadette Bègue; Anaïs Sierra; Sylvain Hanein; Marie-Claude Stolzenberg; Zhi Li; Sandra Pellegrini; Nicolas Garcelon; Marc Jeanpierre; Bénédicte Neven; Isabelle Loge; Capucine Picard; et al. (PLoS ONE, 2018)
Mutations in interleukin-10 receptor (IL-10R) genes are one cause of very early-onset inflammatory bowel disease with perianal lesions, which can be cured by hematopoietic stem cell transplantation. Using a functional test, which assesses responsiveness of peripheral monocytes to IL-10, we identified three unrelated Portuguese patients carrying two novel IL-10RB mutations. In the three patients, sequencing of genomic DNA identified the same large deletion of exon 3 which precluded protein expression. This mutation was homozygous in two patients born from consanguineous families and heterozygous in the third patient born from unrelated parents. Microsatellite analysis of the IL10RB genomic region revealed a common haplotype in the three Portuguese families pointing to a founder deletion inherited from a common ancestor 400 years ago. In the third patient, surface expression of IL-10R was normal but signaling in response to IL-10 was impaired. Complementary DNA sequencing and next-generation sequencing of IL10RB locus with custom-made probes revealed a ≈ 6 Kb duplication encompassing the exon 6 which leads to a frameshift mutation and a loss of the TYK2-interacting Box 2 motif. Altogether, we describe two novel copy number variations in IL10RB, one with founder effect and one preserving cell surface expression but abolishing signaling.